Developing a questionnaire - Gillham, Bill. (London ; New York : Continuum, 2000)
The Pros and Cons of questionnaires. Preparation. Drafting the questions (and answers). Designing the questionnaire. Getting them out and getting them back...
Keywords: Questionnaires; Questionnaires -- Handbooks, manuals, etc